PENGARUH LINGKUNGAN KERJA, BEBAN KERJA, STRESS KERJA, DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN ALFAMART - Ameliani, Julia; Sukarno Putri, Dewi Ika (Faculty of economcs Universitas Singaperbangsa Karawang, 2023)
This research was conducted to analyze the influence of Work Environment, Workload, Job Stress, and Job Satisfaction on Alfamart employees' desire to leave their jobs (Turnover Intention). The population is all Alfamart employees in the Karawang area. The number of samples taken was 100 respondents. Used random sampling technique by selecting respondents randomly. There are two data in this study, namely primary data through questionnaire surveys and secondary data through literature studies. The data processing technique used is multiple linear regression. Based on the research results both partially and simultaneously, it can be concluded that Work Environment, Workload, Job Stress, and Job Satisfaction affect the desire of Alfamart employees to leave their jobs (Turnover Intention).